Temperature-dose relationships with aflatoxin M1 in milk on the brine shrimp (Artemia salina) larvae - Lejla Duraković; Mihaela Blažinkov; Andrea Skelin; Sanja Sikora; Frane Delaš; Mirna Mrkonjić-Fuka; Katarina Huić-Babić; Sulejman Redžepović (Mljekarstvo)
Temperature-dose relationships with aflatoxin M1 (AFM1) were studied using the brine shrimp Artemia salina larvae as an biological indicator in the temperature range from 20 °C to 40 °C. Increase in the incubation temperature resulted in sensitivity increase by the brine shrimp to AFM1. Optimum sensitivity occured at 30 °C. Positive results were obtained at 0.18 μg AFM1 x L-1 of whole pasteurized milk with a mortality of over 15%. Greater than 90 % mortality occurred at dose levels of 0.9 μg AFM1 x L-1 and above. The test can be conducted during 30-60 hours.